La « réflexivité » : une compétence transversale dans la formation des enseignants ? - Marie-Noëlle Hindryckx; Maggy Schneider (Recherches en Éducation)
In French-speaking Belgium, a decree on the training of teachers specifies a set of objectives and of attitudes that must be aimed by any didactic device designed to prepare them for their future job. This set is largely dictated by the model of the "reflective practitioner" able to "have reflective regards to his practice" in order to adapt the way he teaches to the classroom circumstances by a "back and forth" between theory and practice. Two didactic analyzes at the upper secondary level, concerning the biological sciences and the mathematics, allow us to point out knowledge related to the epistemology of the concerned knowledge, whose lack of control, by the students-teachers in initial formation, prevents them to be reflexive in choosing a teaching method and especially feeding it appropriately. Looking at reflexivity, we examine here the concept of cross-curricular competence and its "sensitivity" to more strictly disciplinary knowledge, hoping to add elements into the current debate on this subject whether it is about disciplinary learning or teachers training.